Legal Protection for Third Parties Acquiring Rights in the Management of State Receivables - de Rozari, Petrus; Ratnawati, Elfrida (Universitas Airlangga, 2025)
The government has made various efforts to maximize state revenue, one of which is through issuing Government Regulation No. 28 of 2022 regarding the Management of State Receivables by the State Receivables Committee (Government Regulation 28/2022). According to this regulation, third parties who acquire rights from a debtor or debt guarantor can be held responsible for settling the debt, regardless of the reason. These rights can be seized and auctioned by the state, and the third party can face civil sanctions, travel bans, or even imprisonment. This research aims to examine the legal protection for third parties acquiring rights in the management of state receivables under Government Regulation 28/2022. The research uses a normative method with a descriptive approach. The findings indicate that protection for third parties remains limited due to unclear and vague provisions in Government Regulation 28/2022. This lack of clarity can lead to the abuse of authority by the state, potentially harming third parties acting in good faith. This study is expected to provide insights into the relevance of the regulation and offer recommendations to strengthen legal protections for third parties acquiring rights.